Integrated Genomic and Greenhouse Assessment of a Novel Plant Growth-Promoting Rhizobacterium for Tomato Plant - Guerrieri, Maria Chiara; Fiorini, Andrea; Fanfoni, Elisabetta; Tabaglio, Vincenzo; Cocconcelli, Pier Sandro; Trevisan, Marco; Puglisi, Edoardo (Frontiers in Plant Science, 2021)
Plant growth promoting rhizobacteria (PGPR) can display several plant-beneficial properties, including support to plant nutrition, regulation of plant growth, and biocontrol of pests. Mechanisms behind these effects are directly related to the presence and expression of specific genes, and different PGPR strains can be differentiated by the presence of different genes. In this study we reported a comprehensive evaluation of a novel PGPR Klebsiella variicola UC4115 from the field to the lab, and from the lab to the plant. The isolate from tomato field was screened in-vitro for different activities related to plant nutrition and growth regulation as well as for antifungal traits. We performed a functional annotation of genes contributing to plant-beneficial functions previously tested in-vitro. Furthermore, the in-vitro characterization, the whole genome sequencing and annotation of K. variicola UC4115, were compared with the well-known PGPR Azospirillum brasilense strain Sp7. This novel comparative analysis revealed different accumulation of plant-beneficial functions contributing genes, and the presence of different genes that accomplished the same functions. Greenhouse assays on tomato seedlings from BBCH 11-12 to BBCH > 14 were performed under either organic or conventional management. In each of them, three PGPR inoculations (control, K. variicola UC4115, A. brasilense Sp7) were applied at either seed-, root-, and seed plus root level. Results confirmed the PGP potential of K. variicola UC4115; in particular, its high value potential as IAA producer was observed in increasing of root length density and diameter class length parameters. While, in general, A. brasilense Sp7 had a greater effect on biomass, probably due to its high ability as nitrogen-fixing bacteria. For K. variicola UC4115, the most consistent data were noticed under organic management, with application at seed level. While, A. brasilense Sp7 showed the greatest performance under conventional management. Our data highlight the necessity to tailor the selected PGPR, with the mode of inoculation and the crop-soil combination.